Case Report: A rare case of coronary artery anomaly (right coronary artery-pulmonary artery fistula with diffuse dilatation) - Wang, Xiaoming; Yu, Jie; Chen, Changzheng; Yang, Zhihua; Yang, Lixia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCongenital coronary artery anomalies (CAAs) are rare cardiovascular disorders that often present with non-specific symptoms, making diagnosis and treatment particularly challenging. These anomalies can occur in various forms, including anomalous origin of a coronary artery, coronary artery fistula, and coronary artery tortuosity, among others. The lack of specific symptoms often leads to delayed diagnosis, which can have significant implications for patient outcomes. In addition, the treatment options for CAAs vary depending on the type and severity of the anomaly, posing further therapeutic challenges for healthcare providers.Case presentationThis case report describes a 39-year-old male presenting with heart failure secondary to a giant right coronary artery-pulmonary artery fistula (RCA-PA fistula) accompanied by diffuse aneurysmal dilatation. The patient exhibited acute decompensated heart failure, atrial fibrillation, and severe left ventricular enlargement, initially misattributed to valvular disease. Coronary angiography and surgical exploration confirmed a tortuous, dilated RCA fistula draining into the pulmonary artery, with diffuse aneurysmal changes compromising myocardial perfusion. Due to the complexity of aneurysmal anatomy and high surgical risk, conservative management was adopted, leading to symptomatic improvement.ConclusionsThis case highlights the need for heightened clinical suspicion of CAAs in young patients with atypical heart failure and emphasizes multidisciplinary strategies for managing complex coronary malformations.